OLFACTOMETRY BIOASSAY STUDIES ON BEHAVIOUR OF HOUSE FLIES TOWARDS DIFFERENT FOOD BAITS IN VITRO - S.T. Bino Sundar; T.J. Harikrishnan; Bhaskaran Ravi Latha; T.M.A. Senthil Kumar; G. Sarath Chandra; A. Serma Saravana Pandian; C. Pandian; K. Ambasankar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Food bait preferences of house flies were evaluated using olfactometry bioassays. A single cage dual port glass olfactometer was used to assess preferences of house flies towards sugar, fish meal and molasses in no choice and choice bioassays. Flies were allowed into olfactometer individually, observed for five minutes. Time spent in bait port and decision chamber, number of entries into test/control port and port selected five minutes post-exposure were recorded. In the second study in a four arm acrylic olfactometer, three food baits viz., high fish meal low molasses cake, low fish meal high molasses cake and mango essence were tested In the glass olfactometer, flies showed positive response towards food baits compared to control in no choice bioassay. In choice bioassay, flies preferred fish meal than both sugar and molasses and molasses was preferred over sugar. In four arm acrylic olfactometer bioassay, 43.87, 30.96 and 25.16 per cent flies were attracted to high fish meal low molasses cake, low fish meal high molasses cake and mango essence, respectively. Results revealed that molasses and fish meal based baits can be used in housefly traps. Olfactometry bioassays were found effective in bait preference studies of house flies.